What drives change? A framework to observe and understand broad-‐ scale change in river basins - Cook, Simon E.; Lau, Charlotte; Fisher, Myles J. (CGIAR Challenge Program on Water and Food, 2012)
Development in river basins is strongly influenced by a range of non-‐random factors, called global drivers. These can present a bewildering array of effects that confound concerted action. This report summarizes these effects with the CPWF’s six basins and presents a method of visualizing them together within a process of scenario visualization.